CRISPR/Cas9 genome engineering in PDAC: From preclinical studies to translation and clinical research - Lu, Yanxi; Stoof, Jojanneke; Tanoé, Yaba Rosette; Walsh, Naomi; Bijlsma, Maarten F.; Lei, Huijun; Chen, Tianhui; Grahovac, Jelena; Grützmann, Robert; Pilarsky, Christian (Seminars in Cancer Biology, 2025)
CRISPR/Cas9 technology has emerged as a powerful tool in pancreatic ductal adenocarcinoma cancer (PDAC) research, facilitating the study of genes involved in cell signaling pathways, proliferation, migration, invasion, and chemotherapy resistance. In this review, we discuss the evolution of CRISPR technologies from sophisticated editing techniques to broad screening methods, examine the utility of isogenic models and genetically engineered mouse models (GEMMs). We also explore how CRISPR/Cas9 screens can reveal immune-tumor cell interactions, highlighting the multifaceted role of this technology in PDAC research. Moreover, we emphasize the use of CRISPR technology in diagnostics for CAR-T cell therapies, where CRISPR/Cas9 enhances the precision of targeting malignant cells while minimizing off-tumor effects.
CRIS-Team Scopus Importer:2025-07-25
Keywords: CRISPR/Cas9 Genome Engineering; GEMMs; Pancreatic Ductal Adenocarcinoma; Preclinical studies